Surface-anchored PtNi alloy network over SiO2 (PtNi/SiO2): a versatile carbon-free cathode for proton exchange membrane fuel cells (PEMFCs) - Kumar, Sachin; Yoyakki, Athira; Kurungot, Sreekumar (ACS Applied Engineering Materials, 2024)
The large-scale commercialization of the PEMFCs is hindered due to the high cost of the Pt-based electrocatalysts (Pt/C) and the low durability associated with the oxidation of the carbon support in Pt/C. Many Pt-based carbon-free electrocatalysts have been explored, exhibiting excellent stability and activity, but the performance is further expected to be improved by developing suitable Pt alloy catalysts based on the carbon-free supports. To explore this possibility, we have developed a PtNi/SiO2 alloy system, which acts as a carbon-free electrocatalyst exhibiting enhanced activity for the oxygen reduction reaction (ORR). A half-cell study of PtNi/SiO2 (45 wt%) shows ∼4.3 times higher ORR activity compared to the state-of-the-art Pt/C (40%). The uniform distribution of the PtNi nanoparticles over SiO2 is the crucial feature of the catalyst. PtNi/SiO2 shows better durability even after 5000 cycles compared to the state-of-the-art Pt/C. The catalyst shows a negative shift in the half-wave potential (E1/2) by only 5 mV, which is lower than that of the 11 mV drop incurred by Pt/C. Considering this high activity of the PtNi/SiO2 catalyst for the ORR, we tried to explore the possibility of demonstrating a single-cell PEMFC in the MEA by pairing the catalyst as the cathode along with the Pt/C as the anode. This paired configuration of the single cell is found to be providing promising performance by delivering a current density of 960 mA/cm2 at 0.60 V and a maximum power density of 835 mW/cm2. Thus, this study outlines the possibility of developing potential alloy combinations of Pt on carbon-free substrates and then deploying them as electrodes for PEMFC applications. In the context of mitigating the carbon corrosion-related issues without compromising the intrinsic activities of the catalysts, the development of suitable alloy combinations on various carbon-free substrates is of significant technological advantages. The formation of the alloy phase along with the fine and uniform distribution of the alloy nanoparticles on the SiO2 substrate, followed by its successful deployment as the cathode of a single cell, points toward the scope of exploring material developments in this direction.